Pemberdayaan Karang Taruna Dalam Pengelolaan Sampah Dengan Sistem Bank Sampah - setyawan, suprihono; Tini Utami; Khamidah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to find out the model of waste handling in Ngampel Kulon village, Ngampel District, Kendal Regency, the purpose of this study is to find out the impact of handling waste management using a waste bank system, the method of this research is field research, meaning that the data used as a reference in this study are field facts that are directly related to the research site, The results of this study are known that the waste bank system developed by empowering Karang Taruna has been able to make a positive contribution to the community to care about the household waste produced, then other results explain that handling the waste can help the economy of villagers, although not too large a contribution, in terms of education, sanitation, economy, social and culture, in terms of education, from the efforts of educating citizens to carefully select garbage and know . environment.